Capital Expenditures Increased at Rural Hospitals That Merged Between 2012 and 2015. Issue 5 (September 2020) - Williams, Dunc; Pink, George H.; Song, Paula H.; Reiter, Kristin L.; Holmes, G. Mark
Abstract : EXECUTIVE SUMMARY: The number of rural hospital mergers has increased substantially in recent years. A commonly reported reason for merging is to increase access to capital. However, no empirical evidence exists to show whether capital expenditures increased at rural hospitals after a merger. We used a difference-in-differences approach to determine whether total capital expenditures changed at rural hospitals after a merger. The comparison group (rural hospitals that did not merge during the 2012 through 2015 study period) was weighted using inverse probability of treatment weights. The key outcome measure was logged total capital expenditures. Merging resulted in a 26% increase in capital expenditures and also was associated with a significant improvement in plant age. The postmerger improvement in plant age may have been partially attributable to merger-related accounting changes and partially attributable to increased capital expenses, possibly on long-term asset renovations and replacement. These findings suggest that through mergers, rural hospital board members and executives who have accepted or are considering a merger may improve a hospital's ability to increase capital expenditures. Further, increased capital investments in rural hospitals may be an important signal to the community that the acquirer intends to keep the rural hospital open and continue providing some volume and level of services within the community. Future research should determine how capital is spent after a merger. Abstract : Supplemental Digital Content is available in the text